Critique of "Planetary Normal Mode Computation: Parallel Algorithms, Performance, and Reproducibility" by SCC Team From National Tsing Hua University - Sun, Wei-Fang; Chen, Hung-Hsin; Lin, Shao-Fu; Lin, Yuan-Ching; Wu, Jing-Wei; Lin, En-Te; Chou, Jerry (IEEE transactions on parallel and distributed systems, 2021)
As a special activity of the Student Cluster Competition at SC19 conference, we made an attempt to reproduce the scalability evaluations of a highly paralleled polynomial filtering eigensolver for computing planetary interior normal modes. Our experiments were conducted on a Mars dataset using a small scale 4-node cluster with Intel Skylake CPU architecture, while the original article's were conducted on a Moon dataset using a large scale 256-node supercomputer with Intel CPU Skylake and KNL architectures. This article shares our experiences and observations from our reproducibility activity and discusses our findings on three main sections: the weak scalability, the strong scalability, and the relationships between variables. The results of weak scalability and strong scalability were successfully reproduced. But due to the differences on the problem scale, input dataset, and system architecture, different behaviors regarding the polynomial degree were observed.